CEO turnover and the firm's investment decisions - Weisbach, Michael S. (Journal of Financial Economics, 1995)
This paper examines the relation between management turnover and divestitures of recently acquired divisions. The empirical results indicate that at the time of a management change, there is an increased probability of divesting an acquisition at a loss or one considered unprofitable by the press. The probability increases by about the same amount regardless of whether the change is an apparent age-65 retirement or a resignation. Overall, the results are consistent with a variety of agency-based theories of corporate investment and suggest that management changes are important events for corporations because they lead to reversals of poor prior decisions.